Ketika Awam Membaca Sodom: Intercultural Hermeneutics terhadap Kisah Sodom dalam Kejadian 19 - Vania Sharleen Setyono (Theologia in Loco, 2020)
It is profoundly known that in Indonesia, Genesis 19:1-19 is used to legitimate the movement against homosexual, to discriminate and abuse them. For years, scholars have shaped two different major perspectives in interpreting the passage as a form of God’s punishment towards Sodom. One take side against homosexuals and conclude that the passage speaks about God’s punishment of homosexuality since it is counted as sin while the others take side on homosexuals and agreed that the passage was merely a violation of hospitality. This article expands the aforementioned discourse and broaden the horizon by exploring a new thought based on qualitative research with an intercultural hermeneutics approach developed by Hans de Wit. Along with such an approach, the focus group discussion with ordinary readers resulted that the problem mentioned in Genesis 19 is a matter of patriarchy issues.